The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.5761/atcs.oa.18-00115
|View full text |Cite
|
Sign up to set email alerts
|

Effective Combination of Different Surgical Strategies for Deep Sternal Wound Infection and Mediastinitis

Abstract: Purpose: Timing and ideal reconstructive approach in deep sternal wound infection (DSWI) and mediastinitis still remain controversially debated. We present our own combined surgical strategy of bilateral pectoralis major muscle flap (BPMMF) or omental flap (OF) transposition. Methods: Between July 2010 and July 2016, poststernotomy patients with DSWI and mediastinitis underwent a secondary wound closure with modified BPMMF (Group A, center for disease control class (CDC)-II, n = 21; Group B, CDC-III… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 22 publications
(18 reference statements)
0
25
0
1
Order By: Relevance
“…Because of their high concentration in cancellous bones, fosfomycin and rifampicin proved to be effective in methicillin resistant staph aureus osteomyelitis [Yusef 2018]. Antifungal therapy can be added in the absence of clinical improvement on a broadspectrum antibiotic, even if no fungi are isolated [Abu-Omar 2017;Öztürk 2015;Tewarie 2019;Khanlari 2010]. In a recent study in our institution, the most common pathogen identified was coagulase negative staphylococcus epidermidis followed by S. aureus, pseudomonas and klebsiella [Elassal 2020].…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Because of their high concentration in cancellous bones, fosfomycin and rifampicin proved to be effective in methicillin resistant staph aureus osteomyelitis [Yusef 2018]. Antifungal therapy can be added in the absence of clinical improvement on a broadspectrum antibiotic, even if no fungi are isolated [Abu-Omar 2017;Öztürk 2015;Tewarie 2019;Khanlari 2010]. In a recent study in our institution, the most common pathogen identified was coagulase negative staphylococcus epidermidis followed by S. aureus, pseudomonas and klebsiella [Elassal 2020].…”
Section: Diagnosismentioning
confidence: 99%
“…If the wound is clean and approximation is possible, direct sternal closure, either standard or reinforced, is the ideal solution. Tewarie and colleagues reported superior results, using bilateral pectoralis major muscle flap to the omental flap technique, in patients without sternal bone necrosis, with relatively low recurrence and mortality risks [Tewarie 2019]. Anger and colleagues described a new surgical technique to repair dehiscence using fasciocutaneous flaps from the pectoralis major fascia in 21 patients [Anger 2012].…”
Section: Managementmentioning
confidence: 99%
“…The pedicled omentum flap in comparison to PM or VRAM flaps is discussed controversially (Iacobucci et al, 1989; Milano et al, 1999; Tewarie et al, 2019). Kolbenschlag et al found wound healing disorders in 44% and partial flap necrosis in 4% as well as abdominal wall herniation occurring in 32% of cases (Kolbenschlag et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Mortality in the group of patients with mediastinitis reaches from 47% to 50%. [6][7][8] Unfortunately, the treatment of infectious complications from a sternotomy wound is a complex and multicomponent task. So, for the surgical treatment of severe forms of sternomediastinitis and associated complications are of particular importance for medical and economic importance.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] In this case, fatal outcomes according to the literature range from 10% to 47% or more. [6][7][8] Another of the serious complications after operations performed by the transsternal approach is sternal dehiscence, which may require additional surgical intervention. Sternotomy wound healing is a long process.…”
Section: Introductionmentioning
confidence: 99%